The Effectiveness Of Prenatal Education Interventions On Maternal Anxiety And Birth Outcomes: A Systematic Review - Prihadianto, Dino Gagah; Sari, Ika Novita (Journal of health research and technology, 2025)
Background: Prenatal education interventions are widely implemented in routine antenatal care to enhance maternal and neonatal outcomes. However, evidence regarding their effectiveness remains inconsistent across populations and intervention modalities. Objective: This systematic review aimed to evaluate the effectiveness of prenatal education interventions in reducing maternal anxiety and improving birth-related outcomes. Methods: A systematic search of PubMed, CINAHL, Cochrane Library, and PsycINFO was conducted from database inception to January 2024. Eligible studies included randomised controlled trials (RCTs) and quasi-experimental designs assessing prenatal education interventions with outcomes related to maternal anxiety and birth metrics. Two reviewers performed screening, data extraction, and risk of bias assessments independently, following PRISMA guidelines and utilising the Cochrane Risk of Bias tool. Results: Twenty-eight studies encompassing 5,847 participants were included. Meta-analysis showed a significant reduction in maternal anxiety associated with prenatal education (standardised mean difference [SMD] = –0.42, 95% CI: –0.58 to –0.26, p < 0.001). While significant improvements were observed in maternal knowledge (SMD = 0.65) and self-efficacy (SMD = 0.51), evidence for effects on clinical outcomes such as cesarean delivery rates and birth weight was limited and inconsistent. Conclusions: Prenatal education interventions are effective in reducing maternal anxiety and enhancing maternal knowledge and self-efficacy. However, their impact on clinical birth outcomes remains unclear, highlighting the need for further high-quality studies with standardised methodologies and long-term follow-up.